Endometrial stromal nodule: a rare entity presenting as fibroid polyp - Baghotia, Priyanka; Madaan, Monika; Pujani, Mukta; Soni, Neha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Endometrial stromal sarcoma are rare malignant tumours of the uterus, mainly presenting in premenopausal women, make around 0.2% of all uterine malignancies. The annual incidence of ESS is 1-2 per million women. Diagnosis is usually made post operatively by pathological findings either in endometrial sample or in hysterectomy specimen done for some underlying pathology. Management is total hysterectomy with bilateral salpingo oophorectomy with hormone therapy in hormone sensitive cases. Ovaries can be preserved in young females with early-stage disease. We are presenting a case of endometrial stromal nodule in a 38 years old woman who presented to us with complaint of abnormal heavy uterine bleeding for one and half month.